Cholangiocarcinoma: A Comprehensive Review and Update Guideline - Nugraha, Kadek Nandita; Hardyningrat, Baiq Inna Dwi; Kirana, Devi Chandra; Yahya, Najla Aulia; Ishlahi, Salsabila Dinda Nuril; Kadarisma, Shofia; Djannah, Fathul (Jurnal Penelitian Pendidikan IPA, 2024)
Cholangiocarcinoma is a rare cancer of the gastrointestinal system. However, the prognosis for people with this disease has not improved in the last decade. CCA has a poor prognosis because most cases are diagnosed at an advanced stage and the availability of treatment options is limited.  This literature review aims to provide information regarding the current understanding and guidelines for cholangiocarcinoma. In this literature review, we searched the National Center for Biotechnology Information (NCBI) and Google Scholar using the search keywords "Cholangiocarcinoma", "cholangiocarcinoma management", "cholangiocarcinoma guidelines" taken ScienceDirect, Researchgate, National Comprehensive Cancer Network, and PubMed published in the last 10 years. From various databases, the literature used and according to the selection criteria amounted to 50 articles In the latest articles and the Cancers NCCN Guidelines for Biliary Tract Cancer in 2023, CCA treatment is carried out based on the patient's profile. Targeted therapy is an additional treatment option today by targeting the molecular profile involved in the pathogenesis of CCA. The diagnosis of cholangiocarcinoma is made through histology, radiography, and laboratory examination. Based on the Cancers NCCN Guidelines for Biliary Tract Cancer in 2023, the treatment carried out consists of determining cancer staging, surgery, radiation therapy, and systemic therapy.